(untitled) (Revista científica Olimpia, 2016)
This paper job presents an approach to therapeutic physical process and its link with determining physiological functions for the optimal development of sports training in boxing, such as: electrical memory and brain function. Fundamental concepts such as tolerance to the load, and the concept of biologization, which will determine the basis of its methodology, will be imposed by the analysis of the so-called adaptation law is assumed. Fundamental concepts of rehabilitation are taken over and an analytical approach to the dialectical relationship groups principles of rehabilitation and sports training is done, hefting that within this complex process, the overall result of the lies higher cortical functions in a proper function of the process memorization, where this vital activity is one of the most important identifying the human species as a rational species.